Cultivating rural education : a people-focused approach for states - Howley, Caitlin; Redding, Sam (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Rural life is more complex than it is perhaps credited. This edited volume explores several themes that highlight these complexities, particularly in terms of what they imply for rural teaching and learning. Such themes include the geographic, demographic, and socioeconomic diversity within and across rural communities; the notion that rurality is not a deficit but rather a context; and the array of novel and interesting ways to build upon rural assets and overcome challenges so that rural students are not afforded fewer educational opportunities simply by virtue of their zip code. More practically, this book offers counsel for readers who may be interested learning more about rural circumstances so that they can make informed and responsive decisions about policies and programs targeting rural students, educators, and schools"--